Assessment of Pesticide and Herbicide Residues and Associated Risks in Yam (Dioscorea rotundata) Tubers in Kwande Local Government Area, Benue State, Nigeria - Lakpa, Winifred Avese; Shomkegh, Simon Alyegba; Ekhumelo, David Oriabure (Journal of Science Research and Reviews, 2026)
Yam (Dioscorea rotundata) is a major staple crop in Nigeria, yet its production increasingly relies on herbicides and pesticides to control weeds and pests. This study assessed agrochemical use patterns, perceived health and environmental effects, and residue levels in yam tubers from Kwande Local Government Area. A stratified random sampling design was employed across three production zones (North, South, and West). Thirty farmers were interviewed, and thirty yam tuber samples were analyzed using the QuEChERS extraction method coupled with GC-MS/MS and LC-MS/MS. Method validation showed good linearity (R² ≥ 0.995), recoveries of 80–110%, relative standard deviations below 15%, and limits of quantification of 0.01 mg/kg. Herbicide use was reported by 91.2% of farmers and pesticide use by 73.5%, with metazachlor, atrazine, cypermethrin, chlorpyrifos, glyphosate, and paraquat most frequently detected. Mean herbicide residues ranged from 0.042 ± 0.008 mg/kg (North) to 0.091 ± 0.012 mg/kg (West), while pesticide residues ranged from 0.035 ± 0.009 mg/kg (North) to 0.124 ± 0.018 mg/kg (West). Most values were below or close to international maximum residue limits, though higher concentrations in the West zone suggest more intensive chemical use. Farmers commonly associated agrochemical exposure with skin irritation, respiratory problems, and water and soil contamination. The findings indicate spatial variability in residue burden and highlight potential food-safety and environmental risks. Strengthened regulation, routine residue monitoring, and promotion of integrated pest management are recommended to ensure safer and more sustainable yam production.